Cultural Improvisations: Luigi Riccoboni and the Nouveau Théâtre Italien - McMahan, Matthew. (2017)
Abstract: In this dissertation, I study the expression of improvised national identities that emerged through the collision of diverse forms. The work explores how an eighteenth-century commedia dell'arte troupe led by Luigi Riccoboni, who were invited to establish a theatre in France, wanted to reform the reputation of Italian actors abroad but found they had to adapt and relinquish to the tastes and expectations of a Parisian audience instead. Defining the troupe as a transnational enterprise, I demonstrate how immigration was not an incidental aspect of the troupe but a determining factor of its theatrical decisions. The Italian actors made their theatre a contact zone of Franco-Italian commutation in almost every level of their performance: their prefaces and prologues, their bilingual plays, their style of performance (improvisation), and their adaptation of low genres. The consequence was a hybrid theatre in France in which both parties learned, adapted, and changed in the exchange.; Thesis (Ph.D.)--Tufts University, 2016.; Submitted to the Dept. of Drama.; Advisor: Laurence Senelick.; Committee: Natalya Baldyga, Barbara Grossman, and Mechele Leon.; Keywords: Theater history, and Theater.